Why Differentiation Therapy Sometimes Fails: Molecular Mechanisms of Resistance to Retinoids - Chlapek, Petr; Slavikova, Viera; Mazanek, Pavel; Sterba, Jaroslav; Veselska, Renata (International journal of molecular sciences, 2018)
Retinoids represent a popular group of differentiation inducers that are successfully used in oncology for treatment of acute promyelocytic leukemia in adults and of neuroblastoma in children. The therapeutic potential of retinoids is based on their key role in the regulation of cell differentiation, growth, and apoptosis, which provides a basis for their use both in cancer therapy and chemoprevention. Nevertheless, patients treated with retinoids often exhibit or develop resistance to this therapy. Although resistance to retinoids is commonly categorized as either acquired or intrinsic, resistance as a single phenotypic feature is usually based on the same mechanisms that are closely related or combined in both of these types. In this review, we summarize the most common changes in retinoid metabolism and action that may affect the sensitivity of a tumor cell to treatment with retinoids. The availability of retinoids can be regulated by alterations in retinol metabolism or in retinoid intracellular transport, by degradation of retinoids or by their efflux from the cell. Retinoid effects on gene expression can be regulated via retinoid receptors or via other molecules in the transcriptional complex. Finally, the role of small-molecular-weight inhibitors of altered cell signaling pathways in overcoming the resistance to retinoids is also suggested.
Keywords: mechanisms of resistance; receptory kyseliny retinové; retinoids; retinoidy; Transcription, Genetic; buněčná diferenciace; chemorezistence; differentiation therapy; genetická transkripce; biologický transport; cell differentiation; Animals; lidé; Receptors, Retinoic Acid; Humans; zvířata; Retinoids; Drug Resistance, Neoplasm; Biological Transport; Cell Differentiation